2012
DOI: 10.4111/kju.2012.53.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Biopsy in the Left Lateral Decubitus Position is Less Painful than Prostate Biopsy in the Lithotomy Position: A Randomized Controlled Trial

Abstract: PurposeThe primary objective was to assess whether transrectal ultrasound (TRUS)-guided prostate biopsy in the left lateral decubitus (LLD) position differed from the procedure in the lithotomy position regarding patients' pain perception. The secondary objective was to assess the analgesic effect of intrarectal 2% lidocaine gel in this setting.Materials and MethodsThis single-center, open-label trial enrolled 148 men undergoing prostate biopsy. Then men were randomly assigned to group 1 (LLD position, no lido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
0
10
1
Order By: Relevance
“…In contrast to our results, Kilciler et al [ 12 ] and Lodeta and Lodeta [ 13 ] reported that pain perception during TRUS-guided prostate biopsy is less profound in patients in the LLD position than in the lithotomy position. Those studies suggested that the lithotomy position may be more unpleasant or embarrassing than the LLD position in terms of psychological phenomenon, because the LLD position is a more relaxed and physiological position typically used for sleep and rest.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, Kilciler et al [ 12 ] and Lodeta and Lodeta [ 13 ] reported that pain perception during TRUS-guided prostate biopsy is less profound in patients in the LLD position than in the lithotomy position. Those studies suggested that the lithotomy position may be more unpleasant or embarrassing than the LLD position in terms of psychological phenomenon, because the LLD position is a more relaxed and physiological position typically used for sleep and rest.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite the use of these techniques to reduce pain, many patients still experience a considerable degree of pain during TRUS-guided prostate biopsy [ 9 , 10 ]. Some studies have reported that a patient's pain perception during prostate biopsy is related to the patient's position, such as the left lateral decubitus (LLD) or lithotomy position [ 11 , 12 , 13 ], although this is controversial. Homogeneous data with regard to pain perception during TRUS-guided prostate biopsy are currently sparse, especially in Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the patient’s position could influence the pain level. The lithotomy position is often used in TPBx, which is more uncomfortable than the left lateral position 31 . On the other hand, most patients in the TRBx group complained about inserting the transducer; however, it was overall mild.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to obtain a further relief, the effect of position which is generally selected between lithotomy and conventional left lateral decubitus (LLD) position had been researched (9-11). However, outcomes from several western studies reached contrasting conclusions, and there are no data for Asian population, who have a relatively smaller prostate.…”
Section: Introductionmentioning
confidence: 99%
“…Although techniques including intrarectal lidocaine gel, periprostatic nerve block, and intravenous sedation with opioid drug, have been suggested to decrease the discomfort ( 5 - 7 ), the majority of patients still experience a considerable degree of pain ( 8 ). In an attempt to obtain a further relief, the effect of position which is generally selected between lithotomy and conventional left lateral decubitus (LLD) position had been researched ( 9 - 11 ). However, outcomes from several western studies reached contrasting conclusions, and there are no data for Asian population, who have a relatively smaller prostate.…”
Section: Introductionmentioning
confidence: 99%